The effect of colesevelam treatment on bile acid and lipid metabolism and glycemic control in healthy men - Blahová, T; Peterková, Ludmila; Leníček, Martin; Vlachová, M; Zemánková, Kateřina; Adámková, Věra; Vítek, Libor; Kovář, Jan (Physiological research, 2016)
The treatment of hypercholesterolemia with bile acid (BA) sequestrants results in upregulation of BA synthesis through the classical pathway initiated by cholesterol 7alpha-hydroxylase (CYP7A1). To characterize the detailed dynamics of serum lipid and BA concentrations and the BA synthesis rate in response to treatment with BA sequestrants and to determine whether the -203A/C promoter polymorphism of the CYP7A1 encoding gene (CYP7A1) affects such a response, this pilot study was carried out in healthy men (8 homozygous for the -203A allele and 8 homozygous for the -203C allele of CYP7A1). The subjects were treated for 28 days with colesevelam and blood was drawn for analysis before and on days 1, 3, 7, 14 and 28 of treatment. The response of lipids, BA, fibroblast growth factor-19 (FGF19) and 7alpha-hydroxy-4-cholesten-3-one (C4) to colesevelam did not differ between carriers of -203A and -203C alleles; their data were then aggregated for further analysis. Colesevelam treatment caused immediate suppression of FGF19 concentration and a fivefold increase in CYP7A1 activity, as assessed from C4 concentration, followed by a 17 % decrease in LDL-cholesterol. Although total plasma BA concentrations were not affected, the ratio of cholic acid/total BA rose from 0.25+/-0.10 to 0.44+/-0.16 during treatment at the expense of decreases in chenodeoxycholic and deoxycholic acid.
Keywords: dospělí; Healthy Volunteers; Colesevelam Hydrochloride; fibroblastové růstové faktory; Genotype; LDL-cholesterol; Adult; Bile Acids and Salts; Cholesterol, LDL; cholagoga a choleretika; zdraví dobrovolníci pro lékařské studie; Cholesterol 7-alpha-Hydroxylase; Fibroblast Growth Factors; lidé; Blood Glucose; Lipid Metabolism; Pilot Projects; genotyp; žlučové kyseliny a soli; pilotní projekty; metabolismus lipidů; Male; Thyroid Hormones; hormony štítné žlázy; polymorfismus genetický; cholestenony; alely; kolesevelam; Alleles; Cholagogues and Choleretics; cholesterol-7-alfa-hydroxylasa; lidé středního věku; mužské pohlaví; Polymorphism, Genetic; krevní glukóza; Cholestenones; Middle Aged; Humans